2018
DOI: 10.1002/jcpy.1053
|View full text |Cite|
|
Sign up to set email alerts
|

Don't Count Calorie Labeling Out: Calorie Counts on the Left Side of Menu Items Lead to Lower Calorie Food Choices

Abstract: Providing calorie counts on restaurants’ menus/menu boards is one of the most prominent policy interventions that has been implemented to combat the obesity epidemic in America. However, previous research across multiple disciplines has found little effect of providing calorie counts on calories ordered, leading some to call calorie provision a failed policy. The authors propose that this failure is partly due to not considering how people process information when making food choices: Americans read from left‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 27 publications
1
53
0
Order By: Relevance
“…The apparent widespread prevalence of strategic ignorance may then call for measures that make calorie information harder to ignore. For instance, Ellison et al (2013Ellison et al ( , 2014 show that symbolic traffic light labels enhance the effectiveness of numeric calorie information on menus, and Dallas et al (2019) show that people respond more to calorie information displayed to the left (rather than the usual right) of menu items. Public information campaigns could also be used to make negative health consequences of calorie overconsumption more salient, and thereby increase the perceived cost of ignorance.…”
Section: Resultsmentioning
confidence: 99%
“…The apparent widespread prevalence of strategic ignorance may then call for measures that make calorie information harder to ignore. For instance, Ellison et al (2013Ellison et al ( , 2014 show that symbolic traffic light labels enhance the effectiveness of numeric calorie information on menus, and Dallas et al (2019) show that people respond more to calorie information displayed to the left (rather than the usual right) of menu items. Public information campaigns could also be used to make negative health consequences of calorie overconsumption more salient, and thereby increase the perceived cost of ignorance.…”
Section: Resultsmentioning
confidence: 99%
“…The mean, standard deviation, and sample size for each condition in each experiment reported by Dallas et al (2019) is reproduced in Table 1, together with the key hypotheses used to support their theoretical conclusions. Each of the six reported experiments fully satisfied the hypotheses, thereby providing uniform support for the conclusions.…”
Section: Methodsmentioning
confidence: 99%
“…We evaluated the plausibility of all six studies producing uniform success, by computing estimates of experimental power for replications of each of the studies. These power estimates are based on the statistics reported by Dallas et al (2019), so our analysis starts by supposing that the reported findings are valid and accurate. Since the studies are statistically independent, we can then compute the probability of the full set of studies being uniformly successful by multiplying the estimates of the individual studies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper is also related to the behavioral economics literature documenting inattentive behaviors. 4 For example, Dallas, Liu, and Ubel (2019) find that presenting calorie counts on the left side of menu items lead to lower calorie food choices because Americans read from left to right. For non-health care settings, studies have shown the existence of behavioral biases when employees choose retirement plans and find that employee choice is influenced by default contribution rates (Bernheim, Fradkin, & Popov, 2015), anchoring, goal setting and savings threshold (Choi, Haisley, Kurkoski, & Massey, 2017), income projections (Goda, Manchester, & Sojourner, 2014), and framing effects (Brown, Kling, Mullainathan, & Wrobel, 2008).…”
mentioning
confidence: 99%